ANALISIS KUALITAS LAYANAN MASKAPAI PENERBANGAN LION AIR - Kaysar Wahyu Darmawan; Lamro Benediktus, Marchel Antonio Sinaga, Siti Sahara (CV. ADIBA AISHA AMIRA, 2023)
Airline is an organization that provides flight services for passengers, they rent or own airplanes to provide these services. Airlines have an important role, not only as a mode of transportation for people but also for goods, where airlines can be a medium that helps expedite & shorten the process of transferring passengers from one island/city/country to another island/city/country. There are many types of airlines in Indonesia, in this journal we will discuss PT. Lion Mentari Airlines which is a low-cost carrier based in Jakarta, Indonesia. Lion Air itself is the largest private airline in Indonesia. The service quality of this airline has various public perspectives in assessing the performance of Lion Air airlines